(untitled) (Revista de Ciências Agroveterinárias, 2021)
The objective of this study was to evaluate the phenological behavior and the physical-chemical and productive characteristics of the ‘BRS Carmem’ vine grown in the Western region of Paraná state (Brazil). The evaluation of vines grafted on IAC 572 ‘Tropical’, spaced at 1.5 x 2.5 m, and conducted on a backrest was performed in the harvests 2019/2020 and 2020/2021. Twenty plants representing the experimental orchard of UFPR - Palotina Sector were used. The evaluation of phenological behavior was performed from observation of selected branches, from the fruiting pruning carried out in mid-August, characterizing the duration in days of each of the following subperiods: cotton yolk pruning (PO-GA); pruning to sprouting (PO-BR); pruning to the appearance of inflorescence (PO-AI); pruning to flowering (PO-FL); pruning at the beginning of ripening (PO-IM) of the berries; pruning to harvest (PO-CO), and diagrams were made on a day scale. At the harvest time, the number of bunches per plant, mass of bunches was quantified and from these data the production (kg plant-1) and the productivity (t ha-1) were estimated. To evaluate the must, two bunches per plant were collected, and six berries were collected per bunch to evaluate soluble solids content (SS), titratable acidity (TA), maturation index ratio (SS/TA) and anthocyanin content (mg g-1). For the number of bunches was verified an average of 48 bunches per plant, with an average mass of 133 g. The production per plant and yield estimates were 6.4 kg and 17.1 t ha-1, respectively. The mean levels of SS, AT, SS/AT and anthocyanins were 18°Brix, 0.97% of tartaric acid, 18.4 and 4.97 mg g-1, respectively. Therefore, the productive characteristics and the quality of the ’BRS Carmem’ cultivated in the Western region of Paraná state are within the desirable standards for grape juice preparation.